2021
DOI: 10.3389/fimmu.2020.617522
|View full text |Cite
|
Sign up to set email alerts
|

R848 Is Involved in the Antibacterial Immune Response of Golden Pompano (Trachinotus ovatus) Through TLR7/8-MyD88-NF-κB-Signaling Pathway

Abstract: R848 is an imidazoquinoline compound that is a specific activator of toll-like receptor (TLR) 7/8 and is often used in immunological research in mammals and teleosts. However, the immune responses initiated by R848 through the TLR7/8 pathway in response to bacterial infection remain largely unexplored in teleosts. In the current study, we investigated the antibacterial response and the participating signaling pathway initiated by R848 in golden pompano (Trachinotus ovatus). We found that R848 could stimulate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 76 publications
(60 reference statements)
1
6
0
Order By: Relevance
“…Real-time PCR analysis was employed to further identify the inflammation response of macrophages. Previous have shown that TLR7/8 agonists promoted macrophage polarization through activating NF-κB pathway and inducing the secretion of proinflammatory cytokines [ 27 , 37 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Real-time PCR analysis was employed to further identify the inflammation response of macrophages. Previous have shown that TLR7/8 agonists promoted macrophage polarization through activating NF-κB pathway and inducing the secretion of proinflammatory cytokines [ 27 , 37 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…R848 is a synthetic imidazoquinoline compound, which upon binding to TLR7/8, stimulates the MyD88-dependent signaling pathway. The MyD88-dependent pathway leads to the activation of NF-κB, a transcription factor that induces the expression of a series of pro-inflammatory genes [ 55 , 56 ]. Despite the well-established immunostimulatory activities of the TLR agonists, surprisingly, poly I:C and R848 failed to activate dendritic cells to a significant extent.…”
Section: Discussionmentioning
confidence: 99%
“…The present study on cancer vaccine therapy underscores the importance of adjuvants in combating the immune-suppressive tumor microenvironment. Activation of TLR7/8 receptors in immune cells triggers downstream signaling pathways involving MyD88 which in turn induces the activation of NF-κB and IRFs [ 45 , 46 , 47 , 48 ]. It ultimately leads to the production of pro-inflammatory cytokines and the activation of antigen-presenting cells [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%